An end in sight to early marriage? Evidence from IFPRI’s 2015 survey in rural Bangladesh - Ahmed, Akhter; Sufian, Farha; Ghostlaw, Julie (International Food Policy Research Institute, 2018)
Upon request of the Governance Innovation Unit of the Prime Minister’s Office, Government of the People’s Republic of Bangladesh, IFPRI has prepared this research note using 2015 nationally representative household survey data. This note provides an overview of the state of early marriage in rural Bangladesh, changes in marriage trends over a twenty-year time period, and briefly explores ways to reduce the incidence of early child marriage in Bangladesh as a conduit for development progress.